Systematic theology ; v. 2 - Hodge, Charles, 1797-1878 (Grand Rapids, MI Eerdmans, 1871)
Contents : v. 2 : pt 2, Anthropology; pt 3, Soteriology. Includes bibliographical references.
1952 reprint
Keywords: Theology, doctrinal